Trajectories of new opioid use after hip fracture surgery: a population-based cohort study - Thuy Bui; Miriam T.Y. Leung; Michael J. Dooley; Paul S. Myles; Jenni Ilomaki; J. Simon Bell (PAIN Reports)
Abstract. Introduction:. The global annual incidence of hip fractures is projected to double over the next 20 to 30 years. The rates and risk factors for new persistent opioid use after hip fracture surgery remain poorly quantified. Objective:. To describe trajectories, rates, and risk factors for new persistent opioid use after hip fracture surgery in Australia. Methods:. A retrospective population-based cohort study was conducted using linked administrative health data in Australia. Adults aged ≥30 years discharged from hospital after a first hip fracture surgery between July 2012 and June 2017, opioid-naïve on admission, and alive 12 months postdischarge were included. Group-based trajectory modelling was utilised to determine trajectories and rates of opioid use 12 months postdischarge. Multivariate multinomial logistic regression analysis was performed to identify risk factors for persistent opioid use. Results:. Among 10,309 opioid-naïve patients who had first hip fracture surgery, 5305 (51.5%) used opioids postdischarge. Opioid users were categorised as 58.9% (3127/5305) nonpersistent, 12.6% (670/5305) fluctuating, 12.1% (641/5305) late discontinuation, and 16.3% (867/5305) persistent. Key risk factors for persistent use were total oral morphine equivalent >600 mg in first 30 days postdischarge (relative risk [RR] 13.61, 95% confidence interval [CI] 9.34–19.83), transdermal opioid in the first 30 days postdischarge (RR 7.64, 95% CI 5.61–10.39), and hospital length of stay >60 days (RR 4.31, 95% CI 3.02–6.15). Conclusion:. Among opioid-naïve patients, 16.3% were persistent opioid users at 12 months posthospital discharge. Future research should focus on targeted interventions to address modifiable risk factors to reduce new persistent opioid use in older and vulnerable populations.